An Approach for Determining Optimal Contrast in Visual Cryptography - Juhnke, Jakob; Lefmann, Hanno; Strehl, Volker

Improved Side Channel Attacks on Pairing Based Cryptography - Blömer, Johannes; Günther, Peter; Liske, Gennadij (Constructive Side-Channel Analysis and Secure Design)

On the Analysis of Cryptographic Assumptions in the Generic Ring Model - Jager, Tibor; Schwenk, Jörg (J. Cryptology)

Practical Signatures from Standard Assumptions - Böhl, Florian; Hofheinz, Dennis; Jager, Tibor; Koch, Jessica; Hong Seo, Jae; Striecks, Christoph (Advances in Cryptology - EUROCRYPT 2013, 32nd Annual International Conference on the Theory and Applications of Cryptographic Techniques, Athens, Greece, May 26-30, 2013. Proceedings)

One Bad Apple: Backwards Compatibility Attacks on State-of-the-Art Cryptography - Jager, Tibor; Paterson, Kenneth G.; Somorovsky, Juraj (20th Annual Network and Distributed System Security Symposium, NDSS 2013, San Diego, California, USA, February 24-27, 2013)

Bounded Model Checking of Graph Transformation Systems via SMT Solving - Isenberg, Tobias; Steenken, Dominik; Wehrheim, Heike (Formal Techniques for Distributed Systems - Joint IFIP WG 6.1 International Conference, {FMOODS/FORTE} 2013, Held as Part of the 8th International Federated Conference on Distributed Computing Techniques, DisCoTec 2013, Florence, Italy, June 3-5, 2013. Proceedings)

SPIN as a Linearizability Checker under Weak Memory Models - Travkin, Oleg; Mütze, Annika; Wehrheim, Heike (Hardware and Software: Verification and Testing - 9th International Haifa Verification Conference, HVC 2013, Haifa, Israel, November 5-7, 2013, Proceedings)

A High-Level Semantics for Program Execution under Total Store Order Memory - Dongol, Brijesh; Travkin, Oleg; Derrick, John; Wehrheim, Heike (Theoretical Aspects of Computing - ICTAC 2013 - 10th International Colloquium, Shanghai, China, September 4-6, 2013. Proceedings)

Temporal Reconfiguration Plans for Self-Adaptive Systems - Ziegert, Steffen; Wehrheim, Heike (Software Engineering 2013: Fachtagung des GI-Fachbereichs Softwaretechnik, 26. Februar - 2. März 2013 in Aachen)

Time trends in dietary fat intake in a sample of German children and adolescents between 2000 and 2010: not quantity, but quality is the issue - Libuda, Lars; Alexy, Ute; Kersting, Mathilde (British Journal of Nutrition)
Dietary fat intake in childhood may influence the risk for developing chronic diseases. The objective of the present study was to examine secular trends in the parameters of fat intake between 2000 and 2010 in a sample of German children and adolescents ( n 808) participating in the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) Study. Dietary data from 4380 3 d weighed dietary records were analysed using repeated-measures regression to determine time trends in fat quantity, i.e. the intake of total fat, and in fat quality, i.e. the ratios of SFA, MUFA and PUFA. In young children (2–3 years) and in adolescents (13–18 years), total fat intake remained stable over time, but decreased by 0·08 % of total energy (%E) per year in 4–12-year-old children. In 2010, median fat intake was at the upper end of the recommendations. SFA intake decreased slightly in 2–3- and 4–12-year-old children by 0·09 and 0·05 %E per year, respectively. MUFA and PUFA intakes remained stable in all the age groups except in adolescents. Here, PUFA intake decreased initially, but increased between 2005 and 2010. In 2010, only between 3 and 18 % of the respective age groups had an intake of SFA or PUFA within the recommendations. In conclusion, fat quantity and quality did not change substantially between 2000 and 2010. Fat quality, in particular, needs to be improved, since a large percentage of our sample did not meet the recommended intakes for SFA and PUFA.

11. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung - Gausemeier, Jürgen; Grafe, Michael; Meyer auf der Heide, Friedhelm

Frequencies and demographic determinants of breastfeeding and DHA supplementation in a nationwide sample of mothers in Germany - Libuda, Lars; Stimming, Madlen; Mesch, Christina; Warschburger, Petra; Kalhoff, Hermann; Koletzko, Berthold Viktor; Kersting, Mathilde (European Journal of Nutrition)

Lunch at school, at home or elsewhere. Where do adolescents usually get it and what do they eat? Results of the HELENA Study - Müller, Katrin; Libuda, Lars; Diethelm, Katharina; Huybrechts, Inge; Moreno, Luis A.; Manios, Yannis; Mistura, Lorenza; Dallongeville, Jean; Kafatos, Anthony; González-Gross, Marcela; Cuenca-García, Magdalena; Sjöström, Michael; et al. (Appetite)

Effects of lunch on children’s short-term cognitive functioning: a randomized crossover study - Müller, K; Libuda, Lars; Gawehn, N; Drossard, C; Bolzenius, K; Kunz, C; Kersting, M (European Journal of Clinical Nutrition)

Approaches for an informational separation of powers in learning platforms - Keil, Reinhard; Winkelnkemper, Felix

„Do You Speak Usability?“ – Aktueller Stand des Glossars und des Curriculums für den „Certified Professional for Usability and User Experience (CPUX)“ der German UPA - Fischer, Holger Gerhard; Geis, Thomas; Molich, Rolf; Kluge, Oliver; Heimgärtner, Rüdiger; Hunkirchen, Peter; Polkehn, Knut

Contextual tagging in the coactive knowledge organization - K {\ "u} hnel, Birger

Towards a Holistic Tool for the Selection and Validation of Usability Method Sets Supporting Human-Centered Design - Fischer, Holger Gerhard; Strenge, Benjamin; Nebe, Karsten

Computer science and education - A struggle for creative sovereignty in society? - Keil, Reinhard; Selke, Harald; Winkelnkemper, Felix (FIfF-Kommunikation)

Media contexts - context media - Keil, Reinhard

A Taxonomy-Based Approach Towards NUI Interaction Design - Klompmaker, Florian; Paelke, Volker; Fischer, Holger Gerhard

A Crook is a Crook … But is He Still a Crook Abroad? - On the Effect of Immigration on Destination-Country Corruption - Dimant, Eugen; Krieger, Tim; Redlin, Margarete

A crook is a crook ... but is he still a crook abroad? On the effect of immigration on destination-country corruption - Dimant, Eugen; Krieger, Tim; Redlin, Margarete

Musical Variants in Encoding, Analysis and Visualization - Kepper, Johannes; Roland, Perry; Röwenstrunk, Daniel (Balisage: The Markup Conference 2013)

Bildung für nachhaltige Entwicklung. Den Alltag gestalten – Teilhabe ermöglichen. Verbraucherbildung als Aufgabe von Schule - Oepping, Anke; Schlegel-Matthies, Kirsten (Schule NRW. Amtsblatt des Ministeriums für Schule und Weiterbildung)

Ethik, Konsumentenverantwortung und Verbraucherbildung im Spannungsfeld - Schlegel-Matthies, Kirsten (Haushalt in Bildung und Forschung (HiBiFo))

Fachliche Betreuung des Schwerpunktthemas: Ethik – Konsum – Verbraucherbildung. - Schlegel-Matthies, Kirsten (Haushalt in Bildung und Forschung (HiBiFo))

Ernährungs- und Verbraucherbildung im Unterricht - Oepping, Anke; Schlegel-Matthies, Kirsten

Business Model Representations: A Cross-Disciplinary Review of the Pragmatic, Semantic and Syntactic Foundations of Existing Approaches - John, Thomas; Kundisch, Dennis (Pre-ECIS Workshop on the Digitization in Business Models and Entrepreneurship (DiBME))

A Review of the Effects of Lunch: On Adults’ Short-term Cognitive Functioning - Müller, Katrin; Libuda, Lars; Terschlüsen, Anna Maria; Kersting, Mathilde (Canadian Journal of Dietetic Practice and Research)
Because of widespread irregular lunch consumption by both children and adults, information on the effects of lunch on short-term cognitive functioning is relevant to public health. In September 2012, a MEDLINE search was conducted for studies in which the effects of lunch on cognitive performance were examined. Eleven experimental studies published from 1981 to 1996 were found and evaluated; all involved adults. In three studies, the effects of lunch and lunch skipping were compared; the remaining studies involved a determination of the effects of lunch size and lunch composition. Results of studies in which lunch was compared with no lunch indicate that lunch leads to potential impairment of some aspects of cognitive functioning in the early afternoon. Lunch size may influence cognitive functioning, with impairment more likely to occur after a large lunch than a small lunch. Furthermore, in comparison with low-fat lunches, high-fat lunches seem to result in slower but more accurate responses to some cognitive tasks. However, these suggestions must be viewed with caution, as they are based on only a few studies and are not thoroughly supported by high-quality evidence. In addition, results obtained with adults are not applicable to children. Thus, the potential effects of lunch need further examination in children and adults.

Do Non-Monetary Incentive Systems Matter? Evidence From the Restructuring of a Non-Monetary Incentive System in an Online Community - Mutter, Tobias (Proceedings of the 21st European Conference on Information Systems (ECIS))

Towards an Agile Simulation-based Method for Creating, Evaluating and Selecting Business Models - John, Thomas; Weskamp, Christoph; Kundisch, Dennis; Suhl, Leena (Pre-ECIS Workshop on the Digitization in Business Models and Entrepreneurship (DiBME))

Designing a Web-Based Classroom Response System - Kundisch, Dennis; Herrmann, Philipp; Whittaker, Michael; Neumann, Jürgen; Magenheim, J.; Reinhardt, W.; Beutner, Marc; Zoyke, A. (Proceedings of the Design Science Research in Information Systems and Technologies 2013 (DESRIST))

Does it Pay Off to Bid Aggressively? An Empirical Study - Herrmann, Philipp; Kundisch, Dennis; Rahman, Mohammad (Proceedings of the 46th Hawaii International Conference on System Sciences (HICCS))

Rekrutierung von Müttern mit Säuglingen in einer Interventionsstudie – erste Erkenntnisse aus der PINGU-Studie. - Mesch, C.; Stimming, M.; Wagner, A.; Libuda, Lars; Kersting, M. (Ernährungsumschau International)

Verfahrenstechnische Entwicklung zum Hinterspritzen von Echtholzfurnieren mit Wood-Plastic-Composites (WPC) - Schröder , Cathrin

Untersuchung des Prozessverhaltens neuartiger Einzugzonen-Konzepte für Kautschukextruder - Hallmann, Tobias

Prospective association of protein intake during puberty with body composition in young adulthood - Assmann, K.E.; Joslowski, G.; Buyken, Anette; Cheng, G.; Remer, T.; Kroke, A.; Günther, A.L.B. (Obesity)

Breastfeeding and Its Prospective Association with Components of the GH-IGF-Axis, Insulin Resistance and Body Adiposity Measures in Young Adulthood – Insights from Linear and Quantile Regression Analysis - Günther, Anke L. B.; Walz, Helena; Kroke, Anja; Wudy, Stefan A.; Riedel, Christina; von Kries, Rüdiger; Joslowski, Gesa; Remer, Thomas; Cheng, Guo; Buyken, Anette (PLoS ONE)

Adapting Hardware Systems by Means of Multi-Objective Evolution - Kaufmann, Paul
Reconfigurable circuit devices have opened up a fundamentally new way of creating adaptable systems. Combined with artificial evolution, reconfigurable circuits allow an elegant adaptation approach to compensating for changes in the distribution of input data, computational resource errors, and variations in resource requirements. Referred to as ``Evolvable Hardware'' (EHW), this paradigm has yielded astonishing results for traditional engineering challenges and has discovered intriguing design principles, which have not yet been seen in conventional engineering. In this thesis, we present new and fundamental work on Evolvable Hardware motivated by the insight that Evolvable Hardware needs to compensate for events with different change rates. To solve the challenge of different adaptation speeds, we propose a unified adaptation approach based on multi-objective evolution, evolving and propagating candidate solutions that are diverse in objectives that may experience radical changes. Focusing on algorithmic aspects, we enable Cartesian Genetic Programming (CGP) model, which we are using to encode Boolean circuits, for multi-objective optimization by introducing a meaningful recombination operator. We improve the scalability of CGP by objectives scaling, periodization of local- and global-search algorithms, and the automatic acquisition and reuse of subfunctions using age- and cone-based techniques. We validate our methods on the applications of adaptation of hardware classifiers to resource changes, recognition of muscular signals for prosthesis control and optimization of processor caches.

Plasma-polymerized HMDSO coatings to adjust the silver ion release properties of Ag/polymer nanocomposites - Alissawi, N.; Peter, T.; Strunskus, T.; Ebbert, Christoph; Grundmeier, Guido; Faupel, F. (JOURNAL OF NANOPARTICLE RESEARCH)
In the current work, we study the silver ion release potential and the water uptake through a SiOxCyHz-polymer which is grown from the precursor hexamethyldisiloxane (HMDSO) in radiofrequency (RF) plasma. These layers were deposited on top of two dimensional (2D) ensembles of silver nanoparticles (AgNPs) with nominal thickness of 2 nm on a 20 nm RF-sputtered polytetrafluoroethylene (PTFE) thin film. The composition of the plasma-polymerized HMDSO barriers was varied by changing the oxygen flow during the polymerization process and their thickness was varied as well. Morphology and optical properties of the nanocomposites were investigated using transmission electron microscopy (TEM) and UV-Visible spectroscopy (UV-Vis), respectively. The concentration of the silver ions released from the nanocomposites after immersion in water for several time intervals was measured using inductively coupled plasma mass spectrometry (ICP-MS). Contact angle analysis and electrochemical impedance spectroscopy (EIS) measurements were also performed and results show a strong dependence of the coatings properties and their water uptake on the oxygen content in the coating films and their thickness. Plasma polymerization with increasing the oxygen flow leads to the formation of more hydrophilic thin films with a higher Ag ion release potential. Increasing the thickness of the coatings reduced the amount of the released ions and the rate of the release process was slowed down. This indicates that by tailoring the structure and the thickness of the plasma-polymerized coating films, one can tune the silver ion release properties of Ag/polymer nanocomposites.

Goal-Scenario-Oriented Requirements Engineering for Functional Decomposition with Bidirectional Transformation to Controlled Natural Language. Case Study "Body Control Module" - Daun, Marian; Fockel, Markus; Holtmann, Jörg; Tenbergen, Bastian

Das Verteilungsproblem für mechatronische Systeme - Hüwe, Marcus

Simulationsgestützter Entwurf für Elektrofahrzeuge - Farshizadeh, Emad; Briese, Hermann; Steinmann, David; Stockmann, Lars; Beringer, Steffen; Holler, Dominik; Klobedanz, Kay; Heinzemann, Christian; Peter, Klaus; Leuer, Michael (8. Dortmunder Autotag)
Das Thema Elektromobilität hat in der Fahrzeugindustrie in den letzten Jahren viel Aufmerksamkeit erhalten. Gerade im Bereich der Entwicklung von Steuergeräte-Software ist der Bedarf an frühzeitiger Absicherung hoch. Nur so können Produkteinführungszeiten minimiert und effektiv Entwicklungskosten eingespart werden. Komplexe Werkzeugketten und die verteilte Entwicklung erschweren den Prozess und verlängern die Entwicklungszeit. Das Förderprojekt „Simulationsgestützter Entwurf für Elektrofahrzeuge“, kurz „E-Mobil“, nimmt sich der Herausforderungen einer verteilten Entwicklung von Steuergeräte-Software an. Vier Projektpartner aus Industrie und Forschung untersuchen die Besonderheiten sowohl bzgl. des Entwurfsprozesses, als auch der beteiligten Entwurfswerkzeuge im Vergleich zur konventionellen Fahrzeugentwicklung. Im Fokus stehen die Modellierung und die simulationsgestützte Absicherung in frühen Entwurfsstadien. Die Modellierung umfasst Regelungssoftware sowie die für die Simulation nötigen elektrischen und mechatronischen Komponenten. Die vorliegende Arbeit stellt die Kernthemen sowie aktuelle Ergebnisse aus dem Projekt vor.

Combining Scenario-based and Architecture-based Timing Requirements - Koch, Thorsten
Die in der Automobilindustrie verwendeten eingebetteten Systeme gehören zu den komplexesten eingebetteten Systemen. Die Automobilhersteller sind in der Entwicklung ständig bemüht sowohl die Sicherheit und den Komfort des Fahrers also auch der anderen Insassen zu verbessern. Die meisten der entwickelten Systeme sind sowohl zeit- als auch sicherheitskritisch. Einer Studie von Mercedes-Benz zufolge resultieren 80% der Innovationen in der Automobilbranche aus neuen Elektronikkomponenten, deren Funktionen zu 90% durch Software realisiert wird. Um die steigende Komplexität in der Entwicklung von eingebetteten Systemen zu beherrschen wird in der Automobilbranche immer öfter die modelbasierte Softwareentwicklung anstelle der klassischen Programmierung eingesetzt. Im Requirements Engineering, der ersten Phase der Entwicklung eines Produktes, werden die Anforderungen gesammelt und dokumentiert. Die Dokumentation erfolgt mittels natürlicher Sprache. Modellbasierte Ansätze werden heutzutage höchstens unterstützend eingesetzt. Während des Requirements Engineerings muss der Requirements Engineer sowohl die funktionalen Anforderungen an das zu entwickelnde System als auch seine zeitlichen Anforderungen spezifizieren und analysieren. Die funktionalen Anforderungen umfassen dabei insbesondere die Kommunikation zwischen den verschiedenen Teilsystemen. Szenarien stellen eine intuitive Möglichkeit zur Modellierung von funktionalen Anforderungen dar. Im Rahmen dieser Arbeit wird ein modellbasierter Ansatz zur Modellierung von Szenarien verwendet. Anforderungen an das zeitliche Verhalten werden innerhalb der Architektur spezifiziert. Dazu stehen in der Automobilbranche Architekturbeschreibungssprachen wie EAST-ADL zur Verfügung. Obwohl sowohl funktionale als auch zeitliche Anforderungen an das System spezifiziert und analysiert werden müssen, existiert bisher keine Methodik, die beide Ansätze miteinander kombiniert. Aus diesem Grund wurde im Rahmen dieser Arbeit eine neue Requirements Engineering Methodik entwickelt, die eine systematische und ganzheitliche Spezifikation und Analyse der funktionalen und zeitlichen Anforderungen bereitstellt. Wir haben zwei Modelltransformationen entwickelt, um den Requirements Engineer beim Übergang von den funktionalen zu den zeitlichen Anforderungen zu unterstützen. Die vorliegende Arbeit wird durch eine Evaluierung der Methodik, sowie der Modelltransformationen auf Basis eines Komfortsteuergerätes abgerundet.

An optimized photon pair source for quantum circuits - Harder, Georg; Ansari, Vahid; Brecht, Benjamin; Dirmeier, Thomas; Marquardt, Christoph; Silberhorn, Christine (Optics Express)

Theory of quantum frequency conversion and type-II parametric down-conversion in the high-gain regime - Christ, Andreas; Brecht, Benjamin; Mauerer, Wolfgang; Silberhorn, Christine (New Journal of Physics)

Characterizing entanglement in pulsed parametric down-conversion using chronocyclic Wigner functions - Brecht, Benjamin; Silberhorn, Christine (Physical Review A)

An efficient integrated two-color source for heralded single photons - Krapick, S; Herrmann, Harald; Quiring, V; Brecht, Benjamin; Suche, H; Silberhorn, Christine (New Journal of Physics)

Born in the GDR: Imprinting, Structural Inertia and the Survival Chances of Organizations - Oertel, Simon; Thommes, Kirsten; Walgenbach, Peter (Academy of Management Annual Meeting Proceedings)

Experimentelle und numerische Untersuchungen des Crashverhaltens hybridgefügter Verbindungen - Hein, David; Meschut, Gerson; Hahn, Ortwin; Matzenmiller, Anton; Nelson, Alexander (3. Fügetechnisches Gemeinschaftskolloquium)

Darstellung heterogener 3-D-Szenen in Echtzeit - Petring, Ralf; Eikel, Benjamin; Jähn, Claudius; Fischer, Matthias; Meyer auf der Heide, Friedhelm (11. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung)
Viele virtuelle 3-D-Szenen im industriellen Bereich sind nicht gleichmäßig strukturiert, z.B. weil sie eine stark unterschiedliche Dichteverteilung der Polygone aufweisen. Für solch heterogene Daten existiert kein Algorithmus, der die Gesamtheit der Daten sowohl schnell als auch mit guter Qualität darstellen kann. Die Auswahl der richtigen Algorithmen für einzelne Szenenteile durch einen Experten ist zeitintensiv und in vielen Visualisierungssystemen nicht umzusetzen. Um dieses Problem zu lösen, setzt das hier vorgestellte Multi-Algorithmen-Rendering verschiedene Renderingalgorithmen gleichzeitig ein, um eine virtuelle 3-D-Szene darzustellen. Das Verfahren unterteilt die Szene dafür in einem Vorverarbeitungsschritt automatisch in geeignete Teilregionen und bestimmt deren Eigenschaften. Diese Daten werden zur Laufzeit dazu genutzt, um ständig für den aktuellen Standpunkt des Betrachters eine Abschätzung der Qualität und Laufzeit der zur Auswahl stehenden Renderingalgorithmen zu berechnen. Durch die Lösung eines Optimierungsproblems kann so bei vorgegebener Bildrate durch die passende Zuordnung der Algorithmen zu den Regionen die Bildqualität optimiert werden – bei automatischer Anpassung an die Leistungsfähigkeit der eingesetzten Hardware. In einer experimentellen Evaluierung vergleichen wir die Laufzeit und Bildqualität des Verfahrens mit denen verbreiteter Standardrenderingverfahren.

Spherical visibility sampling : preprocessed visibility for occlusion culling in complex 3D scenes - Eikel, Benjamin

Algorithmische Grundlagen für die Selbstorganisation von Roboterschwärmen - Meyer auf der Heide, Friedhelm (11. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung)

11. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung

On the Admission of Dependent Flows in Powerful Sensor Networks - Cohen, R.; Nudelman, I.; Polevoy, Gleb (Networking, IEEE/ACM Transactions on)
In this paper, we define and study a new problem, referred to as the Dependent Unsplittable Flow Problem (D-UFP). We present and discuss this problem in the context of large-scale powerful (radar/camera) sensor networks, but we believe it has important applications on the admission of large flows in other networks as well. In order to optimize the selection of flows transmitted to the gateway, D-UFP takes into account possible dependencies between flows. We show that D-UFP is more difficult than NP-hard problems for which no good approximation is known. Then, we address two special cases of this problem: the case where all the sensors have a shared channel and the case where the sensors form a mesh and route to the gateway over a spanning tree.
Keywords: Approximation algorithms; Approximation methods; Bandwidth; Logic gates; Radar; Vectors; Wireless sensor networks; Dependent flow scheduling; sensor networks

Gesprochene Korpora des Englischen und ihre Anwendung in der Grammatikforschung - Mindt, Ilka (Grundlagen einer sprachwissenschaftlichen Quellenkunde)

Light scattering by randomly irregular dielectric particles larger than the wavelength - Grynko, Yevgen; Shkuratov, Yuriy; Förstner, Jens (Optical Letters)
Keywords: tet_topic_scattering

MCD: Overcoming the Data Download Bottleneck in Data Centers - Kaiser, Jürgen; Meister, Dirk; Gottfried, Viktor; Brinkmann, André (Proc. IEEE Int. Conf. on Networking, Architecture and Storage (NAS))

A framework for enhancing dependability in self-x systems by Artificial Immune Systems - Rammig, Franz; Stahl, Katharina; Vaz, Gavin Francis (IEEE Int. Symp. on Object/component/service-oriented Real-time distributed Computing (ISORC))

FPGA Implementation of a Second-Order Convolutive Blind Signal Separation Algorithm - Kasap, Server; Redif, Soydan (Proc. IEEE Signal Processing and Communications Conf. (SUI))

Distributing Storage in Cloud Environments - Berenbrink, Petra; Brinkmann, André; Friedetzky, Tom; Meister, Dirk; Nagel, Lars (Proc. Int. Symp. on Parallel and Distributed Processing Workshops (IPDPSW))

Autonomous Resource Management in Dynamic Data Centers - Niehörster, Oliver

Advanced Data Deduplication Techniques and Their Application - Meister, Dirk

Novel Field-Programmable Gate Array Architecture for Computing the Eigenvalue Decomposition of Para-Hermitian Polynomial Matrices - Kasap, Server; Redif, Soydan (IEEE Trans. on Very Large Scale Integration (VLSI) Systems)

File Recipe Compression in Data Deduplication Systems - Meister, Dirk; Brinkmann, André; Süß, Tim (Proc. USENIX Conference on File and Storage Technologies (FAST))

Competitive throughput in multi-hop wireless networks despite adaptive jamming - W. Richa, Andréa; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (Distributed Computing)

Corona: A stabilizing deterministic message-passing skip list - Mohd Nor, Rizal; Nesterenko, Mikhail; Scheideler, Christian (Theor. Comput. Sci.)

Der Kirchenbau zwischen Sakralisierung und Säkularisierung im 17./18. Jahrhundert und heute

An Efficient and Fair MAC Protocol Robust to Reactive Interference - W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (IEEE/ACM Trans. Netw.)

“Between Primitive Hut and Large Scale Housing: The Present of Utopia in Architecture” - Seng, Eva- Maria (Scottish Journal of Arts, Sciences and Scientific Studies)

Artistik und Zirkus als immaterielles Kulturerbe. Was macht eine künstlerische Leistung zum immateriellen Kulturerbe? - Seng, Eva- Maria (Politik und Kultur. Zeitung des Deutschen Kulturrates)

Johann Georg Starcke - Seng, Eva- Maria (Neue Deutsche Biographie Bd. 25)

Rekonstruktion des religiösen Ortes - Seng, Eva- Maria (Die Welt und ihr Double. Abriss und Rekonstruktion, Bauhaus Lectures (im Druck))

Die Vereine für christliche Kunst und die Bildausstattung der Kirchen nach dem 2. Weltkrieg in Westfalen und Württemberg im Vergleich - Seng, Eva- Maria (Kultbild und Andachtsbild)

"Kulturerbe zwischen Globalisierung und Lokalisierung“ - Seng, Eva- Maria (Europäisches Kulturerbe. Bilder, Traditionen, Konfigurationen)

Ehrenpromotion der Fakultät für Kulturwissenschaften der Universität Paderborn an Herta Müller. Paderborn, 29.10.2012. Dokumentation

„Nach der Mauer der Abgrund“? (Wieder-)Annäherungen an die DDR-Literatur

„Wenn ihr zufrieden seid, so ist’s vollkommen“. Vom Hof in Ferrara zur Villa Massimo in Rom oder: Der Autor im Betrieb - Eke, Norbert Otto (Poetiken der Gegenwart. Deutschsprachige Romane nach 2000)

Zu „sagen […], ich unterschreibe Alles, Hunde sind wir ja doch!‘ halte ich des Mannes, des Christen unwürdig“ – Zivilcourage im Vormärz - Eke, Norbert Otto (Jahrbuch zur Liberalismus-Forschung 25)

„Südliches Meer“. Rausch und Ekstase in Gottfried Benns Werk - Eke, Norbert Otto (Benn Forum Band 3 2012/13. Beiträge zur literarischen Moderne [Jahrbuch])

‚Macht nichts, macht nichts, sagte ich mir, macht nichts‘: Herta Müller’s Romanian Novels - Eke, Norbert Otto (Herta Müller)

Widerstehen und Widersprechen [Laudatio auf Herta Müller] - Eke, Norbert Otto (Ehrenpromotion der Fakultät für Kulturwissenschaften der Universität Paderborn an Herta Müller. Paderborn, 29.10.2012. Dokumentation)

„Nach der Mauer der Abgrund“? (Wieder-)Annäherungen an die DDR-Literatur - Eke, Norbert Otto („Nach der Mauer der Abgrund“? (Wieder-)Annäherungen an die DDR-Literatur)

Geklebte Strukturen im Fahrzeugbau – Simulation und Bewertung von Fertigungstoleranzen - Kruschinski, Georg; Matzenmiller, Anton; Bobbert, Mathias; Teutenberg, Dominik; Meschut, Gerson (Leichtbau-Technologien im Automobilbau)

Simulation und Bewertung von Fertigungstoleranzen - Kruschinski, Georg; Matzenmiller, Anton; Bobbert, Mathias; Teutenberg, Dominik; Meschut, Gerson (adhäsion KLEBEN & DICHTEN)

Region-Selective Self-Assembly of Functionalized Carbon Allotropes from Solution - Wang, Zhenxing; Mohammadzadeh, Saeideh; Schmaltz, Thomas; Kirschner, Johannes; Khassanov, Artoem; Eigler, Siegfried; Mundloch, Udo; Backes, Claudia; Steinrück, Hans-Georg; Magerl, Andreas; Hauke, Frank; Hirsch, Andreas; et al. (ACS Nano)

Low-Voltage Self-Assembled Monolayer Field-Effect Transistors on Flexible Substrates - Schmaltz, Thomas; Amin, Atefeh Y.; Khassanov, Artoem; Meyer-Friedrichsen, Timo; Steinrück, Hans-Georg; Magerl, Andreas; Segura, Juan José; Voitchovsky, Kislon; Stellacci, Francesco; Halik, Marcus (Advanced Materials)

Oxygen diffusivity in silicon derived from dynamical X-ray diffraction - Will, J.; Gröschel, A.; Kot, D.; Schubert, M. A.; Bergmann, C.; Steinrück, Hans-Georg; Kissinger, G.; Magerl, A. (Journal of Applied Physics)

Experimentieren lernen auf Englisch - geht das? - Ein bilingual ausgerichtetes Chemieprojekt zur Vermittlung des Erkenntniswegs im Film - Fechner, Sabine; Schüttler, Susanne (MNU)

Konzeption und Inbetriebnahme einer neuen Technikumsanlage zur Absorption und Desorption von CO2 - Hüser, Nicole; Kenig, Eugeny

Kartellrecht der Kreditwirtschaft (Syst. VI) - Krimphove, Dieter (Kölner Kommentar zum Kartellrecht Bd. 4)

Kartellrecht der Versicherungswirtschaft (Syst. VI) - Krimphove, Dieter (Kölner Kommentar zum Kartellrecht Bd. 4)

Eigene Innovation oder Zugangsberechtigung zu fremden Innovationen - Krimphove, Dieter (Handbuch Innovationsmanagement)

Ökonomisch/juristische Konzeption der Innovationen - Krimphove, Dieter (Handbuch Innovationsmanagement)

AT 5 der MaComp: Zusammenarbeit mehrere Wertpapierdienstleistungsunternehmen - Krimphove, Dieter (Kommentar: MaComp Mindestanforderungen an die Compliance-Funktion und die weiteren Verhaltens-, Organisations- und Transparenzpflichten nach §§ 31 ff. WpHG für Wertpapierdienstleistungsunternehmen)

AT 7 der MaComp: Das Verhältnis §§ 33 WpHG ff. zu § 25a KWG - Krimphove, Dieter (Kommentar: MaComp Mindestanforderungen an die Compliance-Funktion und die weiteren Verhaltens-, Organisations- und Transparenzpflichten nach §§ 31 ff. WpHG für Wertpapierdienstleistungsunternehmen)

Brain activity in predictive sensorimotor control for landings: an EEG pilot study. - Baumeister, Jochen; von Detten, S; van Niekerk, SM; Schubert, M; Ageberg, E; Louw, QA (Int J Sports Med)

Instrumented anterior mobilization of the ankle joint increases contralateral somatosensory cortex activation in healthy subjects - Needle, AR; Swanik, CB; Schubert, M; Reinecke, K; Higginson, JS; Baumeister, Jochen

Quelltextgenerierung für LEGO Mindstorms-Roboter - Geismann, Johannes (Berichtsband der Informatiktage 2013: Smarte Sichten, smarte Schichten)
Die Komplexität von mechatronischen Systemen wird stetig größer. MechatronicUML (MUML) ist eine Methode zur Entwicklung für Software von mechatronischen Systemen. Im Rahmen einer Bachelorarbeit wurde ein bestehender Quelltextgenerator für MUML-Modelle so erweitert, dass Quelltext für ein Echtzeitbetriebssystem generiert werden kann, welches auf einem LEGO Mindstorms-Roboter installiert ist.